Evaluation of the anterior mandibular donor site one year after secondary reconstruction of an alveolar cleft: 3-dimensional analysis using cone-beam computed tomography. Issue 8 (October 2015) - van Bilsen, M.W.T.; Schreurs, R.; Meulstee, J.W.; Kuijpers, M.A.R.; Meijer, G.J.; Borstlap, W.A.; Bergé, S.J.; Maal, T.J.J.
Abstract The aim of this study was to analyse changes in the volume of the chin after harvest of a bone graft for secondary reconstruction of an alveolar cleft. Cone-beam computed tomographic (CT) scans of 27 patients taken preoperatively, and immediately and one year postoperatively, were analysed, and 3-dimensional hard-tissue reconstructions made. The hard-tissue segmentation of the scan taken one year postoperatively was subtracted from the segmentation of the preoperative scan to calculate the alteration in the volume of bone at the donor site (chin). A centrally-orientated persistent concavity at the buccal side of the chin was found (mean (range) 160 (0-500) mm3). At the lingual side of the chin, a central concavity remained (mean (range) volume 20 (0-80) mm3). Remarkably, at the periphery of this concavity there was overgrowth of new bone (mean (range) volume 350 (0-1600) mm3). Re-attachment of the muscles of the tongue resulted in a significantly larger central lingual defect one year postoperatively (p = 0.01). We also measured minor alterations in volume of the chin at one year. Whether these alterations influence facial appearance and long term bony quality is to be the subject of further research.